Socialist thought in ruins. What can we expect? - Morin, Edgar (MATRIZes, 2022)
This is an essay published in Le Monde, in 1993, in which the author discusses the meaning of socialism from a possibility of reviewing its constitutive aspects and its aspirations for the construction of a better society. Questioning determinist ideas defined by a rationality eager for progress, Edgar Morin calls us to reflect on the need for a civilizing project aimed at "transforming the human species into humanity"; being able to respond to a context of increasing complexity, which seems to reach its apex today, making this text an important manifesto on hope for the construction of social relations more and more human.